David Lynch, Embodiment and Mediality: Dealing With a Human Form - Benedict Welch (Film-Philosophy, 2022)
This article considers the role of disembodiment in the visual art and films of David Lynch. This line of inquiry, I argue, allows us to consider the ways scholars do and do not conceptualise the relationship between Lynch’s works of different mediums. Specifically, I pursue the conviction that Lynch’s preoccupation with an injured or fragmented body corresponds to his intermedial creative practice. I turn my attention to Lynch’s early short film The Alphabet (1968) which exemplifies how the violence inflicted on the body represents the violence wreaked by the separation of art into different media. Using Jacques Rancière’s definition of mediality and his idea of the sensorium, I offer a new perspective on the questions of disembodiment that manifest in tricky and unpredictable bodies in Lynch’s work and thus on how we should read Lynch’s output as joined up across mediums. 1